A Moral Underpinning for Legal Ethics - Hibbitt, Tory (Kent Law Review, 2014)
This paper explores the ideal basis, qua moral theory, for legal ethics. It favours David Luban’s interpretation of Fuller’s theory of natural law. Luban’s theory offers a pragmatic moral standard that is flexible in nature, with the primary aim being the protection of human dignity. The advantages of Luban’s theory are fleshed out by contrasting it with those of Kant and Mill. An examination of Kant’s Categorical Imperative, and Mill’s Utilitarianism illuminates the need for a less rigid moral underpinning of legal ethics. Luban’s theory serves as a more convincing moral compass as opposed to a strictly prescribed principle. It allows for subjective moral values, autonomy, and personal judgement in its overarching pursuit of safeguarding human dignity. If there is to be a moral theory as the foundation for legal ethics, it must be one that is practical and attainable, whilst allowing for the revision and evolution of laws. Luban’s theory does precisely this.